PENERAPAN MODEL TEAMS GAMES TOURNAMENT BERBASIS LESSON STUDY KELAS 4 SEKOLAH DASAR NEGERI 032 TARAKAN - Herniwati, Herniwati; Al Wahid, Sucahyo Mas'an; Saputra, Ady (Universitas Borneo Tarakan, 2024)
The learning process tends to position teachers as the center of learning or the only source of learning. This study is to improve the learning outcomes of grade 4 students through the implementation of the lesson study-based teams games tournament model. This type of research is qualitative with a case study. The subjects of the study were 17 students in grade 4 at elementary school 032 Tarakan based on purposive sampling of learning outcome data. Data collection instruments used observation sheets, interview sheets and documentation. The results of the study showed that there was an increase in the learning outcomes of grade IV students after the implementation of the lesson study-based teams games tournament learning model. At the syntax stage of class presentation (plan), namely designing learning plans on theme 4 sharing work and theme 6 my ideals. Then at the syntax stage of learning in groups, games and matches (do) it was found that the results of the success indicators achieved were the percentage of cognitive aspect values through the student worksheets at the initial meeting of 46.66% and increased to 100% on the student worksheets at the next meeting. In addition, data obtained on affective assessment at the initial meeting, the percentage of students' affective assessment was 91.99% and increased to 94.66% at the next meeting, while the percentage of students' psychomotor aspects at the initial meeting was 67.11% and increased to 83.11% at the next meeting. The syntax of group awards from the results of reflection (see) there is a difference in student activity to be active in asking questions and answering to achieve group awards.